RITUXIMAB IN PEDIATRIC RHEUMATOLOGY - E.I. Alexeeva; R.V. Denisova; S.I. Valieva; T.M. Bzarova; A.O. Lisitsyn ("Paediatrician" Publishers LLC, 2010)
The article presents literature review on the role of B-lymphocytes in pathogenesis of rheumatologic diseases and on the administration of chimeric anti-CD20 monoclonal antibodies - rituximab - for treatment of systemic lupus erythematosus, systemic vasculitis, juvenile dermatomyositis, and juvenile arthritis in children. Results of studies showed that rituximab has good tolerability, efficacy and safety in children's rheumatologic practice.Key words: children, B-lymphocytes, rituximab, treatment, depletion.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):54-62)